Valoración del producto gastronómico ancestral como parte de la manifestación cultural del Cantón Valencia de la Provincia de Los Ríos, año 2019 - Villon Ripalda, Lourdes Katherine (2019)
The present investigation was carried out in the canton of Valencia which was dominated “Assessment of the ancestral gastronomic product as part of the cultural manifestation of the of canton Valencia the Province of Los Ríos, year 2019”. In this work it was proposed to identify the typical gastronomy of the canton, elaborate an ancestral gastronomic route and make an ancestral gastronomic recipe book of the Canton Valencia. To obtain reliable results in the objectives, a survey was carried out on 381 people belonging to the economically active population. In the second objective, key points were taken in GPS to use these coordinates in the program, using a program, the map was created that allowed us to geographically locate the places. 51% of the respondents stated that if the ancestral gastronomic product is valued, 64% of the population express that the representative dish is: the baking of pig, however, there is also the sausage broth, dry of chicken duck and roasts; It should be noted that a tab was used to identify each typical dish and perform the inventory. A linear route or linear circuit was developed that allows to know four stops where dishes mentioned above are offered; Finally, the recipe book was carried out showing the ingredients that should be used for the preparation step by step, in this way it was possible to verify and show that the inhabitants are willing to collaborate in the economic, tourist and social development of this area. Keywords: Gastronomic product, tourist route, recipe book.